2017
DOI: 10.1002/fuce.201600209
|View full text |Cite
|
Sign up to set email alerts
|

Direct Formic Acid PEM Fuel Cell with Electrospun Carbon Nitride Nanofibers as Cathode Catalyst

Abstract: Carbon nitride (CNx) nanofiber is tested as a cathode catalyst in the direct formic acid proton exchange membrane (PEM) fuel cell at room temperature. CNx nanofiber is synthesized by electrospinning technique with polyacrylonitrile (PAN) as a supporting polymer and carbon black and Nafion® dispersion as fillers. Potassium permanganate (0.144M) is used as oxidant, due to its higher reduction potential (1.7 V) as compared to O2. CNx nanofibers show fuel cell activity with current density (23 mA cm−2) and power d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…For efficient use in DFAFCs, apart from high activity toward ORR, the cathode catalysts need to be FA tolerant because the crossover of fuel from the anode to the cathode side may create a mixed potential at the cathode, resulting in low efficiency. Pt supported on composite substrates such as TiO 2 /C (Timperman et al, 2011), oleylamine‐functionalized Pd (Y. Shi et al, 2014), and CN x nanofibers (Jindal et al, 2017) were reported to be tolerant towards FA. Furthermore, catalysts such as Ir and its alloys (K. Lee et al, 2011), CoSe/C (Nekooi et al, 2010), RuSe (Timperman et al, 2011), Ru x Se y /C (Gago et al, 2011) as well as Co and Fe deposited on nitrogen‐doped carbon nanotubes (CNTs) (Abd Lah Halim et al, 2019) were reported to show high selectivity to ORR and good FA tolerance.…”
Section: Dfafc Electrochemical Reactionsmentioning
confidence: 99%
“…For efficient use in DFAFCs, apart from high activity toward ORR, the cathode catalysts need to be FA tolerant because the crossover of fuel from the anode to the cathode side may create a mixed potential at the cathode, resulting in low efficiency. Pt supported on composite substrates such as TiO 2 /C (Timperman et al, 2011), oleylamine‐functionalized Pd (Y. Shi et al, 2014), and CN x nanofibers (Jindal et al, 2017) were reported to be tolerant towards FA. Furthermore, catalysts such as Ir and its alloys (K. Lee et al, 2011), CoSe/C (Nekooi et al, 2010), RuSe (Timperman et al, 2011), Ru x Se y /C (Gago et al, 2011) as well as Co and Fe deposited on nitrogen‐doped carbon nanotubes (CNTs) (Abd Lah Halim et al, 2019) were reported to show high selectivity to ORR and good FA tolerance.…”
Section: Dfafc Electrochemical Reactionsmentioning
confidence: 99%
“…Characteristics of electrospinning include high tunability over the fiber dimension and morphology, high versatility over the type of polymer that can be electrospun, and possible functionalization of the fibers [3][4][5][6][7][8]. This makes it a technique of choice for a wide range of applications, for example tissue engineering, drug delivery, filtration, catalyst support, sensors and energy devices [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%